Diamond supercapacitors: Progress and perspectives. Issue 3 (June 2021) - Yu, Siyu; Yang, Nianjun; Liu, Shetian; Jiang, Xin
Graphical abstract: Highlights: Fundamentals of electrical double layer capacitors, pseudocapacitors, and redox-electrolyte-enhanced supercapacitors. Progress and achievements of different diamond supercapacitors. Future perspectives of diamond supercapacitors. Abstract: High performance supercapacitors (SCs) need to employ superior capacitor electrodes. Among various capacitor electrodes, diamond and related materials have been recognized as one of the best capacitor electrodes. This is because of their excellent stability, large potential windows, rich surface chemistry, varied surface terminations, and the possibility to enhance their surface areas. Herein, this article summarizes recent progress and achievements regarding the synthesis of nanostructures, particles, hybrid materials and pseudocapacitive composites of diamond and related materials. The applications of these materials for the SC construction are then overviewed. The performance of reported diamond electrical double layer capacitors, pseudocapacitors, redox-electrolyte-enhanced SCs, and metal-ion capacitors is reviewed in detail. Some diamond SC devices and demonstrators are highlighted. The future perspectives of diamond SCs are further outlined and discussed.